THE EFFECT OF AUDIO VISUAL MEDIA ON IMPROVING KNOWLEDGE REPRODUCTIVE AND SEXUAL HEALTH RIGHTS - Wahyulia Rizqia Umami; Zakiyatul Faizah; Ratna Dwi Jayanti (UNIVERSITAS AIRLANGGA, 2022)
Background: Social norms that assume that talking about reproductive health is taboo and that basic education is often misunderstood can encourage adolescents to engage in uncontrolled sexual behavior. Lack of knowledge regarding the importance of reproductive health can increase deviations in social behavior. The number of early marriages that occurred in Ponorogo increased by about 50 percent in the range from January to August 2020. The purpose of the research was to know about the effect of audiovisual media on improving knowledge about reproductive and sexual health rights in SMK N 1 Ponorogo. Methods: The design of this study is quasi-experimental with the research design of the pretest-posttest questionnaire with control group design. The total sample of 84 respondents was taken using a simple random sampling technique. The population used is class XII students of SMK N 1 Ponorogo. The sample used met the inclusion criteria, namely a healthy state, class XII and was willing to be a respondent. The independent variable is education using audio-visual media about reproductive and sexual health rights and the dependent variable is the level of knowledge. The collected data were analyzed using the Wilcoxon Signed Rank Test. Results: There was an influence of providing education through audio-visual media on increasing knowledge about reproductive and sexual health rights in the experimental group after being given audio-visual media on health education with a p value (0.001). Conclusions: Providing audio visual media about reproductive health education can improve knowledge and information in adolescents. Keywords : knowledge, reproductive and sexual health rights, audio-visual media